2004
DOI: 10.1007/s10658-004-0815-2
|View full text |Cite
|
Sign up to set email alerts
|

Citrus viroid II variants associated with ?Gummy Bark? disease

Abstract: A viroid etiology for citrus gummy bark (CGB) disease of sweet orange is supported by the similarity of symptom expression to cachexia disease of mandarins and tangelos caused by the hop stunt viroid (HSVd) related citrus viroid II (CVd-II), as well as the detection of CVd-II variants in CGB infected Washington navel and Do¨rtyol sweet orange, a Turkish cultivar. A survey was made of 67 clones of CVd-II related variants recovered from severe CGB symptomatic and non-symptomatic trees of the same cultivars growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
0
13
2
Order By: Relevance
“…Partially replacing sole R or B or R/B mixture by green light did not cause differences in leaf area, SLA, shoot: root ratio and biomass of MM and cry1a mutant. This contradicts previous ndings on green light responses, but in those studies PPFD also increased when adding G (Kim, 2005; Samuolienė et al, 2012; Novičkovas at al., 2012). Zhang et al (2011) reported that 40% green light induced a shade avoidance response in Arabidopsis seedlings, whereas 10% did not.…”
Section: Phys Play Role In Blue Light Effects On Elongationcontrasting
confidence: 73%
See 1 more Smart Citation
“…Partially replacing sole R or B or R/B mixture by green light did not cause differences in leaf area, SLA, shoot: root ratio and biomass of MM and cry1a mutant. This contradicts previous ndings on green light responses, but in those studies PPFD also increased when adding G (Kim, 2005; Samuolienė et al, 2012; Novičkovas at al., 2012). Zhang et al (2011) reported that 40% green light induced a shade avoidance response in Arabidopsis seedlings, whereas 10% did not.…”
Section: Phys Play Role In Blue Light Effects On Elongationcontrasting
confidence: 73%
“…Higher G intensity also increased contents of photosynthetic pigments in Arabidopsis seedlings, and biomass and photosynthetic parameters in leaves of lettuce (Golovatskaya and Karnachuk, 2008;E mova et al, 2013;Johkan et al, 2012;Muneer et al, 2014). Lettuce plants grown in a mixture of R, B and G (RBG) had larger speci c leaf area (SLA) but lower stomatal conductance (gs) compared with RB alone, where the total light intensity of RBG was higher than that of RB (Kim, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing confirmed that Ca‐909 lacks the ‘cachexia cluster’ (Reanwarakorn and Semancik 1999). Furthermore, population profiles and genetic lineages also indicate that the Ca‐909 variant may not be a cachexia disease agent (Önelge et al. 2004; Vidalakis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex RT-qPCR has been reported to be a robust and economical detection tool for a broad range of different plant pathogens ( Genetic variability within a pathogen species is often a drawback in the design of primers and MGB probes for qPCR. Despite their small genome, genetic variability within viroid species has been reported for different hosts and geographical areas (Amari et al, 2001;Fadda et al, 2003;Flores et al, 2005;Ito et al, 2002;Lin et al, 2015;Mohamed et al, 2009;Önelge et al, 2004;Owens, 2008;Semancik et al, 1994;Semancik and Duran-Vila 1999;Szychowski et al, 2005;Wang et al, 2013). Therefore, all available CEVd, CBCVd, and HSVd genome sequences in GenBank were used to design the assays, and a wide range of samples from different hosts and geographical areas were used to validate and evaluate the assays.…”
Section: Discussionmentioning
confidence: 99%